Proceedings of the 33rd Southeastern Symposium on System Theory (Cat. No.01EX460)
DOI: 10.1109/ssst.2001.918537
|View full text |Cite
|
Sign up to set email alerts
|

Detecting network intrusions via a statistical analysis of network packet characteristics

Abstract: Absrracf-With the growing threat of abuse of network resources, it becomes increasingly important to be able to detect malformed packets on a network and estimate the damage they ean cause. Carefully constructed, certain types of packets can cause a victim host to crash while other packets may be sent only to gather necessary information about hosts and networks and can be viewed as a prelude to attack. In this paper, we collect and analyze aU of the IP and TCP packets seen on a network that either violate exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…For instance, in Ref. [27] Bykova et al identify several categories of malformations observed in TCP/IP packets that include:…”
Section: Example 2: Protocol Misuses In Intelligence Gathering and Otmentioning
confidence: 99%
“…For instance, in Ref. [27] Bykova et al identify several categories of malformations observed in TCP/IP packets that include:…”
Section: Example 2: Protocol Misuses In Intelligence Gathering and Otmentioning
confidence: 99%
“…Much of the work in this area models normal network behaviour so that behaviour that does not satisfy the constraints of normal network behaviour is assumed to be caused by intrusion. Examples of this work include [1].…”
Section: Related Workmentioning
confidence: 99%
“…We developed a QoS management system [6] that deals with soft and dynamic QoS requirements by providing management services (implemented by a set of management processes and resource managers that support the following: (1) Detecting that an application's run-time behaviour does not satisfy the application's QoS requirements. This violation of QoS requirements (also called a symptom) is a manifestation of a fault in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Up till now the basic idea of network anomaly discriminant lies in anomaly detection method, provided by Denning in 1987 [1]. That is to say, according to abnormality situations of audit statement in monitoring system, the bad behaviors (i.e.…”
Section: Introductionmentioning
confidence: 99%